Effect of major nutrients on yield of ginger (Zingiber officinale Rose.) intercropped in coconut garden - Jayachandran, K Ajithkumar, B K (Journal of Spices and Aromatic Crops, 2001)
The effect of different levels of nitrogen, phosphorus and potassium on the yield of ginger (Zingiber officinale Rosc.) grown as an intercrop in a coconut garden was studied in a field experiment conducted at Coconut Research Station, Balaramapuram, Thiruvanathapuram, Kerala. Significant increases in leaf production, leaf area index and dry matter production, crop growth rate and uptake of nutrients were resulted from higher dose of fertilizers. Fertilizer recommendation for ginger grown under open condition (N:P:K @.75:50:50 kg ha-1) is insufficient for ginger intercropped in coconut gardens. A higher fertilizer dose of N:P:K @ 150:100:100 kg ha-1 is necessary for increasing the yield of ginger grown as an intercrop in coconut garden.